Calculating Method and Experimental Verification on Freezing Time of Finite Cyclical Foodstuff - 赖建波; 臧润清; 车晶 (Zhileng xuebao)
Accurate calculation of freezing time of foods is important for optimum design and operation of a food freezer. In this study, freezing time of foods was divided into three stages that are pre-cooling time, freezing time, and super cooling time. The dynamic calculation models were constructed for these three stages respectively. Based on the study of the finite cyclical foodstuff, the models are confirmed to be reliable by comparing the calculating results with the experimental data.